Appointing and Remunerating Insolvency Practitioners in Japan: The Roles of Japanese Courts. Issue 1 (27th March 2017) - Steele, Stacey
Abstract: Japanese courts play an important role in appointing and remunerating insolvency practitioners. This article examines the roles of courts on the basis of academic and practitioner literature, judicial decisions and interviews with practitioners and former and current judicial officers. First, the article focuses on the methods used to appoint practitioners and the evolution of the system at the Tokyo District Court, Japan's busiest insolvency jurisdiction. Second, the article examines the courts' roles in reviewing and setting practitioners' remuneration through another case study from the Tokyo District Court. Practices trialled and developed in Tokyo are often adapted for local purposes around Japan. The article argues that the courts' involvement has helped to keep the cost of resolving corporate insolvency in Japan down. The review and setting of remuneration deserves particular attention with the increasing prevalence of pre‐packaged and informal restructuring that prima facie appears to allow for greater freedom to set remuneration as between the practitioner and debtor‐client. The article uses a case study to demonstrate that pre‐packaged restructuring is still influenced by the court, however, arguing that the relationship between the court and practitioners remains important. Finally, the article suggests that changes in Japanese insolvency practice and external factors may require the courts and the profession to revisit approaches to appointing and remunerating practitioners. Copyright © 2017 INSOL International and John Wiley & Sons, Ltd.